Blockchain in accounting: A systematic review of financial reporting transparency and fraud mitigation in Indonesia - Arif Rahman Hasdik; Andi Muhammad Syukur Hidyatullah; Nadya Annisa Nasaruddin (Privietlab, 2026)
The crisis of public trust due to massive financial scandals demands a fundamental transformation in financial reporting architecture. Blockchain technology has emerged as a transformative solution owing to its decentralization, real-time transparency, and immutability. This study aims to analyze the implementation of blockchain in enhancing accounting transparency through a Systematic Literature Review (SLR) using the PRISMA 2020 protocol. The analysis was conducted on 42 high-quality articles filtered from Scopus, Sinta, and Garuda databases (2016–2026) and evaluated using the JBI Critical Appraisal instrument. The findings reveal three main mechanisms through which blockchain enhances transparency: Triple-Entry Accounting (TEA), real-time audit automation, and the reduction of information asymmetry. TEA introduces a layer of cryptographic verification (